Developing core outcome sets (cos) and core outcome measures sets (coms) in cosmetic gynecological interventions: Protocol for a development and usability study - Stergios K. Doumouchtsis (2022)
Background: Studies evaluating cosmetic gynecological interventions have followed variable methodology and reported a diversity of outcomes. Such variations limit the comparability of studies and the value of research-based evidence. The development of core outcome sets (COS) and core outcome measures sets (COMS) would help address these issues, ensuring a minimum of outcomes important to all stakeholders, primarily women requesting or having experienced cosmetic gynecological interventions. Objective: This protocol describes the methods used in developing a COS and COMS for cosmetic gynecological interventions. Methods: An international steering group within CHORUS, including health care professionals, researchers, and women with experience in cosmetic gynecological interventions from 4 continents, will guide the development of COS and COMS. Potential outcome measures and outcomes will be identified through comprehensive literature reviews. These potential COS and COMS will be entered into an international, multi-perspective web-based Delphi survey where Delphi participants judge which domains will be core. A priori thresholds for consensus will get established before each Delphi round. The Delphi survey results will be evaluated quantitatively and qualitatively in subsequent stakeholder group consensus meetings in the process of establishing "core" outcomes. Results: Dissemination and implementation of the resulting COS and COMS within an international context will be promoted and reviewed. Conclusions: This protocol presents the steps in developing a COS and COMS for cosmetic gynecological interventions. Embedding the COS and COMS for cosmetic gynecological interventions within future clinical trials, systematic reviews, and practice guidelines could contribute to enhancing the value of research and improving overall patient care.